Menumbuhkan Humanisme Religius dengan Pembelajaran Pendidikan Agama Islam - Mudzakar Aziz (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2021)
Religious humanism is a religious value that places humans as humans, as well as efforts to humanize science while still paying attention to the responsibilities of hablun minallah and hablun minan naas. problems, such as the moral degradation of students which are still difficult to handle, for example, ignorance of the surrounding environment, selfishness, and so on. The problem of moral and moral degradation is increasingly widespread against the background of several factors, including the negative impact of advances in information technology which is increasingly out of control. The focus of the research in this study are How is PAI Learning in growing religious humanism? This research is a descriptive qualitative research. The results of this study are as follows: 1. The concept of PAI learning in fostering religious humanism, includes the use of the concept of exemplary, question and answer, discussion, project and practice. 2. Religious humanist character of students at MA Al Islamiyah Mojoasem: respect and obedience to educators, mutual respect for each other, have high learning motivation, diligent and obedient to worship and patient